Paleolithic inhabitants of Denisova Cave - Shunkov M.V.; Kozlikin M.B. (Вестник археологии, антропологии и этнографии, 2024)
Based on paleogenetic analysis of anthropological remains from Denisova Cave in Altai Mountains, a previously unknown population of fossil people, the Denisovans, was discovered, and a complex picture of their interaction with Neanderthals was established. Currently, 17 skeletal remains of Paleolithic hominins discovered in the cave have been identified, and fragments of ancient human DNA have been isolated from its Pleistocene deposits. This work is devoted to the characteristics of the Denisova Cave inhabitants based on a comprehensive analysis of currently known paleoanthropological and paleogenetic data. We show that the oldest human remains in Altai were found in the basal deposits of the Denisova Cave. They belong to the Denisovans, hominins that share a common ancestor with Neanderthals but a different population history. The lower culture-bearing layers with finds from the initial stage of the Middle Paleolithic contain fragments of genomes that differ from the Denisovan genomes from the overlying sediments, indicating the existence of two different populations of Denisovans. The earliest evidence of the appearance of Neanderthals in Altai was also found in Denisova Cave. A complete genome sequence was isolated from the phalanx of the foot, which received the conditional name Altai Neanderthal. Between the populations of Neanderthals and Denisovans in Altai, there was a regular exchange of genetic material.